Geomorphological mapping of terrestrial and marine areas, northern Malta and Comino (central Mediterranean Sea) - Mariacristina Prampolini (Journal of Maps, 2017)
This paper presents an integrated geomorphological map of terrestrial and marine areas of northern Malta and Comino (central Mediterranean Sea) at 1:25,000 scale. The map is the result of terrestrial and marine analyses of different types of data such as aerial photos, digital terrain model of the seafloor and its acoustic backscatter image. The research is intended to emphasise the relationships and continuity of geomorphological features of both the land- and sea-scape, and outline their evolution. The map highlights the occurrence of fluvial, karst and gravity-induced landforms both on land and on the seafloor, such as palaeo-fluvial channels, sinkholes and landslides, which were shaped during sea level lowstands of the last glacial cycle.